Interest Rate Uncertainty, Spread and Economic Activity: Empirical Evidence in Malaysia - Abd. Ghafar Ismail; Zulkefly Abdul Karim; Mohd.Azlan Shah Zaidi; Hairunnizam Wahid (Universitas Islam Indonesia, 2006)
The determination of the term structure of interest rate is of great interest to both policy makers and researchers in finance and economics. Not surprisingly, a large body of literature (among others, Fisher (1907), Cox, Ingersoll and Ross (1985), and Longstaff (2000). The uncertainty of interest rates is another variable that has been widely investi-gated, since it measures uncertainty of a macroeconomic nature. It is important both for its effect on the macroeconomic variables (interest rates, investments, etc.) and its effect on in-dividual or firm investment decisions (see, for example, Siegfred (2000)). Therefore, this study will focus on the interest rate spread resulting from default risk and attempts to explain how and why the risk spread leads business cycles. This study also contribute to the existing literature by looking at the interest rate uncertainty that plays a critical role in explaining the interest rate spread and economic activity. Furthermore, the finding shows that interest rate uncertainty embodies useful information in term of predicting the growth rate of indus-trial production.Key words: interest rate uncertainly, interest rate spread, economic activity